2016
DOI: 10.1016/j.celrep.2016.05.018
|View full text |Cite
|
Sign up to set email alerts
|

The Long Non-coding RNA HIF1A-AS2 Facilitates the Maintenance of Mesenchymal Glioblastoma Stem-like Cells in Hypoxic Niches

Abstract: Long-non-coding RNAs (lncRNAs) have an undefined role in the pathobiology of glioblastoma multiforme (GBM). These tumors are genetically and phenotypically heterogeneous with transcriptome subtype-specific GBM stem-like cells (GSCs) that adapt to the brain tumor microenvironment, including hypoxic niches. We identified hypoxia inducible factor 1 alpha-antisense RNA 2 (HIF1A-AS2) as a subtype-specific hypoxia inducible lncRNA, up-regulated in mesenchymal GSCs. Its deregulation affects GSC growth, self-renewal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
174
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(185 citation statements)
references
References 60 publications
9
174
0
2
Order By: Relevance
“…GSC subclass stratification, initially performed by gene signature (Mao et al, 2013; Mineo et al, 2016; Ricklefs et al, 2016), was further validated by analysis of subclass-enriched proteins and gene microarray, categorizing them as either proneural-like (P) or mesenchymal-like (M) (Figure S1A, B). To verify whether the expression of miR-128 can drive molecular subclass speciation, we screened both subpopulations of GSCs, and found that expression of miR-128 varied coherently between them, being the lowest in M GSCs (Figure 1A, S1C–E).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…GSC subclass stratification, initially performed by gene signature (Mao et al, 2013; Mineo et al, 2016; Ricklefs et al, 2016), was further validated by analysis of subclass-enriched proteins and gene microarray, categorizing them as either proneural-like (P) or mesenchymal-like (M) (Figure S1A, B). To verify whether the expression of miR-128 can drive molecular subclass speciation, we screened both subpopulations of GSCs, and found that expression of miR-128 varied coherently between them, being the lowest in M GSCs (Figure 1A, S1C–E).…”
Section: Resultsmentioning
confidence: 99%
“…Mycoplasma testing was routinely performed by PCR. Mesenchymal and proneural subclass classification was performed by gene expression profiling as previously described (Mineo et al, 2016). Stable GSCs with either overexpression or knock-down of miR-128 in M and P GSCs were created by lentiviral infection with pCDH-miR-128 and anti-miR-ZIP128 respectively (Godlewski et al, 2008; Peruzzi et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, interaction of IMP2 with the long ncRNA (lncRNA) MyoD was found to prevent translation of its associated transcripts, N-Ras and C-myc (Gong et al 2015). A study conducted on mesenchymal GBM showed that IMP2 interacts with the hypoxia-sensitive lncRNA HIF1a-AS2 and facilitates its association with its target transcripts, such as HMGA1 (Mineo et al 2016). IMPs also appear to have the potential to destabilize lncRNAs, as shown by the ability of IMP1 to recruit the CCR4-NOT deadenylase complex to degrade the liver-specific lncRNA HULC (Hammerle et al 2013).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Bromodomain protein BRD4 promotes the expression of HOTAIR to regulate the cell cycle of glioma cells (6). In a hypoxic microenvironment, HIF1A-AS2 facilitates the maintenance of mesenchymal glioblastoma stem-like cells (7). A lncRNA transcribed from the 5-prime end of the HOXA transcript HOXA11-AS contributes to the malignant progression of glioblastoma (8).…”
Section: Introductionmentioning
confidence: 99%